Mixed data in inverse spectral problems for the Schrödinger operators - Hatinoglu, Burak (Journal of spectral theory, 2021)
We consider the Schrödinger operator on a finite interval with an L^1 -potential. We prove that the potential can be uniquely recovered from one spectrum and subsets of another spectrum and point masses of the spectral measure (or norming constants) corresponding to the first spectrum. We also solve this Borg–Marchenko-type problem under some conditions on two spectra, when missing part of the second spectrum and known point masses of the spectral measure have different index sets.